Blood stream infections with Candida species: a prospective study in a tertiary care center - Arun Divakar; M. Gopala Krishna Pillai; Anil Kumar V; Rithesh Reddy Gundam (International Journal of Medical Research and Review, 2017)
Aims and Objectives: To study the profile of blood stream infections with Candida species, their current epidemiological trend at our setting, clinical management, resistance trends and outcome in terms of mortality.Methods: This is a prospective observational study conducted among all adult in-patients, at AIMS, Kochi from August 1st 2014 to February 28th 2016, both in wards and ICUs, who have positive isolates of Candida species in bloodstream infection among the positive blood culture samples. Incidence rate of Candidemia was calculated and distribution of Candidemia with respect to characteristics like age, gender, comorbid illness, mechanical ventilation, prior antibiotic therapy, prolonged ICU stay.Results: Out of 1600 blood stream infection isolates, Candidemia was fourth most common blood stream isolate infection in our study with an incidence rate of 7.5%. Candida tropicalis was the predominant species in our study (30.8%). Mortality rate due to Candidemia was (61%). Urethral catheterization, Central venous access, neutropenia at presentation, prior antibiotic therapy, renal failure, Dialysis patients, prolonged ICU stay were some of the risk factors found to be statistically significant in assessing the mortality of patients in our study with a p value of <0.001.Conclusion: All patients with Candidemia should be treated with an antifungal agent at the earliest without any delay, as delay causes increase in mortality. All vascular catheters should be removed to help clear Candida from blood more quickly. Improved survival was found with the use of an Echinocandin and the removal of central venous catheters.